Preparation method of nitrogen-doped porous carbon nanoflower catalyst for zinc-air battery

By using nitrogen-doped porous carbon nanoflower catalyst, the problem of insufficient catalytic activity of zinc air battery cathode ORR is solved, and the power performance of zinc air battery is improved. The preparation process of this catalyst is environmentally friendly and low-cost, and is suitable for large-scale applications.

CN118136864BActive Publication Date: 2025-02-21HUNAN INSTITUTE OF SCIENCE AND TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211536412.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-02
Publication Date
2025-02-21
Estimated Expiration
2042-12-02

AI Technical Summary

Technical Problem

The cathodic oxygen reduction reaction (ORR) catalytic activity of zinc air batteries is insufficient, resulting in poor high-power performance of zinc air batteries, and the high cost and scarcity of existing precious metal catalysts, which limits their large-scale applications.

Method used

Using nitrogen-doped porous carbon nanoflower catalyst, nanoflower structures are formed through the water bath chelation of amino acids and zinc chloride and the oxidative autopolymerization function of levodopa. Finally, micropores and mesoporous are prepared by volatile zinc atoms at high temperature. The catalyst of structure.

Benefits of technology

It improves the catalytic activity of oxygen reduction reaction, improves the power performance of zinc air batteries, and uses environmentally friendly raw materials, low cost, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 221202155929
    Figure 221202155929
  • Figure 221202155939
    Figure 221202155939
  • Figure 221202155952
    Figure 221202155952
Patent Text Reader

Abstract

The invention relates to the technical field of zinc-air battery cathode materials, and in particular to a method for preparing a nitrogen-doped porous carbon nanoflower catalyst for zinc-air batteries. The catalyst material (NCNF-m) uses amino acids (glutamic acid and lysine) as carbon and nitrogen sources, zinc chloride is chelated with amino acids to form amino acid zinc chelates containing coordination bonds, and levodopa is added to an aqueous solution system to adjust the morphology, and finally high-temperature heat treatment is performed to evaporate Zn atoms to form pores to obtain the catalyst material. The invention has a simple preparation process and a unique material structure, and the prepared catalyst can be used for the cathode of a zinc-air battery to achieve efficient catalysis of an oxygen electrode reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of zinc-air battery cathode materials, and in particular to a method for preparing a nitrogen-doped porous carbon nanoflower catalyst for zinc-air batteries. The method uses green and environmentally friendly amino acids as raw materials, adds levodopa to form a nanoflower structure, and obtains a method for improving ORR catalytic activity. Background Art

[0002] Zinc-air batteries (ZABs) are regarded as promising energy storage devices in the future and have received great attention due to their advantages such as high specific energy, low cost, environmental friendliness and high safety. However, the oxygen reduction reaction (ORR) at the cathode is constrained by slow kinetics, resulting in poor high-power performance of ZABs. It is well known that precious metal catalysts are currently the most effective oxygen reduction catalysts, but their large-scale application is seriously affected by their high cost and scarcity. Therefore, it is of great significance to develop non-precious metal oxygen reduction catalysts ZABs with high performance and low cost.

[0003] Nitrogen-doped carbon materials have attracted much attention in recent years due to their excellent catalytic properties. Traditional methods for preparing nitrogen-doped carbon materials usually involve directly pyrolyzing macromolecular precursors containing C and N to synthesize carbon nanomaterials, or later performing N-doping on the prepared carbon materials. The former often requires secondary pyrolysis, acid or alkaline etching and other methods to adjust the N-doping type and increase the specific surface area, while the latter often results in irregular layered structures and insufficient specific surface area. The above methods have complex experimental processes and high costs. Therefore, the present invention uses amino acids as nitrogen and carbon sources, and utilizes the self-polymerization function of L-DOPA to assemble the sheets formed by amino acid zinc coupling into nanoflower structures, creating a large number of mesoporous structures to expose more active

[0004] The zinc atoms in the precursor are volatilized at high temperature, which not only preserves the morphology of the nanoflowers, but also generates a large number of microporous structures and structural defects.

[0005] The authorization announcement number is: CN 110038612 A, entitled A N-doped microporous carbon sphere ORR catalytic material, preparation method and application thereof, discloses a method for preparing a catalyst, but the pyrrole used as a raw material in the preparation method of the catalyst is not environmentally friendly, and the catalyst has only a large number of micropores but no mesopores. The presence of micropores can increase the specific surface area of ​​the catalyst and provide a high-density active site, while mesopores are more conducive to the generation of more structural defects and the transport of electrolytes.

[0006] In order to solve the above technical problems, the present invention provides a new technical solution to consider the synthesis of NCNF-m materials, improve the catalytic activity of oxygen reduction, thereby improving the power performance of zinc-air batteries, and particularly relates to a method for preparing nitrogen-doped porous carbon nanoflower catalysts for zinc-air batteries. Summary of the invention

[0007] In view of the problems existing in the prior art, the present invention provides a method for preparing a nitrogen-doped porous carbon nanoflower catalyst for a zinc-air battery. The catalyst prepared by the present invention has good application prospects in electrocatalysis, and compared with other catalysts, the raw materials are green and environmentally friendly and have low cost, the preparation process is simple, and it is conducive to large-scale production.

[0008] To achieve the above object, the present invention adopts the following specific scheme to achieve: a preparation method of nitrogen-doped porous carbon nanoflower catalyst for zinc-air battery, the catalyst uses amino acid as nitrogen source and carbon source, and uses L-dopa to adjust its morphology. Specifically, zinc glutamate and zinc lysine obtained by chelating amino acid (glutamic acid, lysine) with zinc chloride in water bath are dehydrated and condensed by condensing agent to form a sheet structure, and the added L-dopa is also condensed by condensing agent and amino acid.

[0009] The zinc chelate is connected, and the oxidative self-polymerization function of L-DOPA is used to assemble the flakes into a nanoflower structure, and finally the zinc atoms in the precursor are volatilized at high temperature to obtain the nitrogen-doped porous carbon nanoflower catalyst material NCNF-m. Among them: the molar ratio of the amino acid to zinc chloride is 5:3; the molar ratio of zinc lysine, zinc glutamate and L-DOPA is 1:1:1 ~1:1:5.

[0010] The present invention also provides a method for preparing a nitrogen-doped porous carbon nanoflower catalyst for a zinc-air battery, the method comprising the following steps:

[0011] Step 1: weigh a certain amount of glutamic acid and dissolve it in deionized water, and add a certain amount of zinc chloride. After dissolution, adjust the pH of the solution and perform chelation in a water bath to form an amino acid zinc chelate (zinc glutamate);

[0012] Step 2: weigh a certain amount of lysine and dissolve it in deionized water, and add a certain amount of zinc chloride. After dissolution, adjust the pH of the solution and perform chelation in a water bath to form an amino acid zinc chelate (zinc lysine);

[0013] Step 3: Quantitatively weigh the zinc glutamate and zinc lysine obtained in step 1 and step 2, and add a quantitative amount of levodopa to dissolve them in an acidic aqueous solution, then add the condensation agent EDC·HCl, react for a certain period of time to dehydrate and condense the three, and add DIEA to adjust the pH of the solution to alkaline, so that it precipitates to form a NCNF-m precursor;

[0014] Step 4: The NCNF-m precursor obtained in step 3 is subjected to high-temperature segmented calcination in a nitrogen atmosphere. First, the material is carbonized by low-temperature calcination to maintain a stable structural morphology. Then, the zinc in the material is vaporized under high-temperature calcination to form a porous carbon material. Finally, the final product NCNF-m is obtained after cooling.

[0015] Preferably, in step 1 and step 2, the molar ratio of amino acid (glutamic acid, lysine) to zinc chloride is 5:3.

[0016] Preferably, in the step 1, in the preparation conditions of zinc glutamate, hydrochloric acid and ammonia water are used to make the solution pH=6.5, and the water bath conditions are 90° C. for 30 min;

[0017] Preferably, in the step 2, in the preparation conditions of zinc lysine, hydrochloric acid and ammonia water are used to make the solution pH=8, and the water bath conditions are to react at 60° C. for 2 h.

[0018] Preferably, in step 3, the molar ratio of zinc glutamate: zinc lysine: levodopa is 1:1:0.5 to 1:1:5.

[0019] Preferably, in step 3, the acidic condition is pH = 4.5 ~ 5, and the condensing agent is 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl)

[0020] Preferably, in step 3, the reaction time of adding EDC·HCl is 2 h.

[0021] In step 3, N,N-diisopropylethylamine (DIEA) is used to adjust the pH of the material to a pH of 7.

[0022] Preferably, the order of high temperature staged calcination in step 3 is firstly heating to 350°C, keeping the temperature for 2 h, then heating to 1050°C, keeping the temperature for 2 h, and the heating rate is 2-5°C min -1 .

[0023] Compared with the prior art, the present invention has the following beneficial effects: the amino acids and levodopa used in the scheme are environmentally friendly raw materials; the morphology and mesoporous structure of the catalytic material can be adjusted by controlling the amount of levodopa; the calcined precursor formed by the dehydration condensation reaction of amino acid zinc and levodopa can form a large number of microporous structures by calcining and volatilizing zinc at high temperature, which increases the specific surface area and provides high-density active sites to enhance the catalytic activity. The experimental process is simple and easy to operate. The obtained catalyst material has a unique structure and excellent catalytic performance, and has broad application prospects in the field of energy storage and conversion. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The XRD pattern of the sample NCNF-1 obtained in Example 2 is

[0025] Figure 2 1 is the SEM image of the sample NCNF-m obtained in Example 1, Example 2, Example 3 and Example 4.

[0026] Figure 3 These are the TEM and HRTEM images of sample NCNF-1 obtained in Example 2.

[0027] Figure 4 It is the nitrogen adsorption-desorption curve and pore size distribution curve of the sample NCNF-1 obtained in Example 2.

[0028] Figure 5 It is the LSV diagram of the samples NCNF-m and Pt / C obtained in Example 1, Example 2, Example 3 and Example 4.

[0029] Figure 6 This is a schematic diagram of lighting an LED light board using a liquid zinc-air battery using the sample NCNF-1 obtained in Example 2 as a cathode catalyst. DETAILED DESCRIPTION

[0030] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] In the description of the present invention, it should be noted that the directions or positional relationships indicated by the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc. are based on the directions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the devices or elements referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.

[0032] In the description of the present invention, it should be noted that unless otherwise clearly specified and limited,

[0033] The terms "installed", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0034] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below through the accompanying drawings and embodiments. However, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.

[0035] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0036] A method for preparing a nitrogen-doped porous carbon nanoflower catalyst for zinc-air batteries, wherein the catalyst uses amino acids as nitrogen and carbon sources, and uses L-dopa to adjust its morphology. Specifically, zinc glutamate and zinc lysine obtained by chelating amino acids (glutamic acid, lysine) with zinc chloride in a water bath form a sheet structure through dehydration condensation with a condensing agent, and the added L-dopa is also connected to the amino acid zinc chelate through a condensing agent, and the sheet is assembled into a nanoflower structure by utilizing the oxidative self-polymerization function of L-dopa, and finally the zinc atoms in the precursor are volatilized at high temperature to obtain the nitrogen-doped porous carbon nanoflower catalyst material NCNF-m. Wherein: the molar ratio of the amino acid to zinc chloride is 5:3; the molar ratio of zinc lysine, zinc glutamate and L-dopa is 1:1:1 to 1:1:5.

[0037] The coupling-calcination treatment method adopted in the present invention can have existing technical solutions, and can also adopt the following technical solutions.

[0038] A method for preparing nitrogen-doped porous carbon nanoflower catalyst for zinc-air battery:

[0039] Example 1

[0040] (1) Weigh 7.36g of glutamic acid and add it to deionized water. After it is completely dissolved, weigh 4.089g of zinc chloride and add it. Add hydrochloric acid or ammonia water dropwise to maintain the pH of the system at 6.5. Heat and stir in an oil bath at 90℃ for 30min, then let it stand to room temperature, centrifuge and dry to obtain the zinc glutamate product.

[0041] (2) Weigh 7.3 g of glutamic acid and add it to deionized water. After it is completely dissolved, weigh 4.089 g of zinc chloride and add it. Add hydrochloric acid or ammonia water dropwise to maintain the pH of the system at 8. Heat and stir in an oil bath at 60°C for 2 h, then let it stand to room temperature, centrifuge and dry to obtain the zinc lysine product.

[0042] (3) Weigh 1.074 g of zinc glutamate obtained in step (1), 1.067 g of zinc lysine obtained in step (2), and finally weigh 0.296 g of levodopa, add deionized water, adjust the pH to 4.5-5 with hydrochloric acid, dissolve them under acidic conditions and control their pH value, then add EDC.HCl to react for 2 h, and finally adjust the pH to 7 with DIEA. The resulting precipitate is centrifuged and freeze-dried to obtain NCNF-m precursor.

[0043] (4) The calcined precursor obtained in step (3) was placed in a tubular furnace and calcined under a nitrogen atmosphere. The temperature was first raised to 350°C and kept at this temperature for 2 h at a heating rate of 2°C min-1. -1 Then continue to heat up to 1050 ℃, keep warm for 2 h, and the heating rate is 5 ℃ min -1 .

[0044] The sample obtained by the above steps was named NCNF-0.5.

[0045] Example 2

[0046] (1) Same as step (1) in Example 1

[0047] (2) Same as step (2) in Example 1.

[0048] (3) Weigh 1.074 g of zinc glutamate obtained in step (1), 1.067 g of zinc lysine obtained in step (2), and finally weigh 0.592 g of levodopa, add deionized water, adjust the pH to 4.5-5 with hydrochloric acid, dissolve them under acidic conditions and control the pH value, then add EDC.HCl to react for 2 h, and finally adjust the pH to 7 with DIEA. The resulting precipitate is centrifuged and freeze-dried to obtain NCNF-m precursor.

[0049] (4) Same as step (4) in Example 1.

[0050] The sample obtained by the above steps was named NCNF-1.

[0051] Example 3

[0052] (1) Same as step (1) in Example 1

[0053] (2) Same as step (2) in Example 1.

[0054] (3) Weigh 1.074 g of zinc glutamate obtained in step (1), 1.067 g of zinc lysine obtained in step (2), and finally weigh 1.184 g of levodopa, add deionized water, adjust the pH to 4.5-5 with hydrochloric acid, dissolve them under acidic conditions and control their pH value, then add EDC.HCl to react for 2 h, and finally adjust the pH to 7 with DIEA. The resulting precipitate is centrifuged and freeze-dried to obtain NCNF-m precursor.

[0055] (4) Same as step (4) in Example 1.

[0056] The sample obtained by the above steps was named NCNF-2.

[0057] Example 4

[0058] (1) Same as step (1) in Example 1

[0059] (2) Same as step (2) in Example 1.

[0060] (3) Weigh 1.074 g of zinc glutamate obtained in step (1), 1.067 g of zinc lysine obtained in step (2), and finally weigh 2.96 g of levodopa, add deionized water, adjust the pH to 4.5-5 with hydrochloric acid, dissolve them under acidic conditions and control their pH value, then add EDC.HCl to react for 2 h, and finally adjust the pH to 7 with DIEA. The resulting precipitate is centrifuged and freeze-dried to obtain NCNF-m precursor.

[0061] (4) Same as step (4) in Example 1.

[0062] The sample obtained by the above steps was named NCNF-5.

[0063] Figure 1 This is the XRD pattern of the sample NCNF-1 obtained in Example 2. As shown in the figure,

[0064] Sample NCNF-1 has only two obvious peaks at 2θ = 24° and 44°, which belongs to graphite carbon.

[0065] The (002) and (101) diffraction patterns show no other impurity peaks, indicating that the prepared material has formed a graphite structure. This result also shows that when the calcination temperature is 1050°C, the Zn atoms are completely volatilized without any residue.

[0066] Figure 2 1 is the SEM image of the sample NCNF-m obtained in Example 1, Example 2, Example 3 and Example 4. Figure 2(a) is the SEM of NCNF-0.5 in Example 1. It can be seen from the figure that it is a flower-like nanostructure assembled by nanosheets, but the connection between the nanosheets is poor. Figure 2 (b) The SEM of NCNF-1 in Example 2 shows that its porous nanosheet structure is tightly connected and assembled into a flower-like morphology, and a large number of mesoporous structures are formed between the nanosheets. The flower-like morphology can expose more active sites and form a good three-dimensional conductive network, which is conducive to high-performance electrocatalytic activity. As the amount of L-DOPA added increases, the nanoflower structure is gradually destroyed, as shown in Figure 2 (c) SEM of NCNF-2 in Example 3 shows that the nanosheet structure is randomly condensed, while Figure 2 (d) The SEM of NCNF-5 in Example 4 shows that the nanoflower structure is completely collapsed. The accumulation of nanosheets causes serious aggregation of active sites and blockage of some mesoporous structures, resulting in poor catalytic performance. Figure 2 It can be found that adjusting the amount of L-DOPA added can adjust the morphology of NCNF-m, thereby designing it in a direction that is beneficial to ORR catalysis.

[0067] Figure 3 These are the TEM and HRTEM images of sample NCNF-1 obtained in Example 2. Figure 3 (a) TEM of NCNF-1, which once again verifies that NCNF-1 has a typical nanoflower-like structure. Figure 6 (b) HRTEM of NCNF-1 shows a large number of white spots, indicating the presence of micropores in NCNF-1. This also verifies that high-temperature volatilization of zinc will cause the material to form a large number of micropores, increase the porosity, and thus improve the ORR catalytic performance.

[0068] Figure 4 It is the nitrogen adsorption-desorption curve and pore size distribution curve of the sample NCNF-1 obtained in Example 2. As shown in the figure, the NCNF-1 adsorption-desorption curve belongs to the IV type, and is accompanied by a typical capillary condensation phenomenon, indicating that it has a unique porosity, which verifies that high-temperature volatilization of zinc forms a large number of microporous structures. The inner figure is the pore size distribution curve. It can be seen from the figure that the NCNF-1 catalyst mainly presents mesoporosity, indicating that a mesoporous structure is formed between the nanosheets. It is reported that the presence of micropores is conducive to the increase of specific surface area and provides a high density of active sites, while mesopores are conducive to the generation of more structural defects, which is conducive to the penetration of electrolytes and electron transfer. Therefore, the micropores and mesopores in carbonaceous materials are conducive to the catalytic activity of the zinc-air battery cathode.

[0069] Figure 5 The LSV diagrams of the samples NCNF-m and Pt / C obtained in Example 1, Example 2, Example 3 and Example 4 are shown in the figure. As shown in the figure, NCNF-1 exhibits the highest onset potential (Eonset =0.97 V, half-wave potential (E 1 / 2 = 0.87 V) and limiting current density (J L = 6.20 mAcm 2 ), these values ​​are very close to those of commercial Pt / C, showing excellent ORR catalytic performance. NCNF-5 exhibits poor onset potential and half-wave potential, which indicates that L-DOPA has an important influence on the regulation of the mesoporous structure, which plays a vital role in the ORR catalytic activity.

[0070] Figure 6 This is a schematic diagram of lighting an LED light board using a liquid zinc-air battery using the sample NCNF-1 obtained in Example 2 as a cathode catalyst.

[0071] The catalyst of the present invention is a nitrogen-doped porous carbon nanoflower material, which uses amino acids as carbon and nitrogen sources, and forms a nanoflower structure with micropores and mesopores through the function of oxidative self-polymerization of L-DOPA and the means of high-temperature calcination and volatilization of zinc. On the one hand, in the nitrogen-doped carbon material, the lone pair of electrons carried by nitrogen can also enhance the electron density of the carbon material, which is conducive to the carbon atoms adsorbing more O2, thereby promoting the ORR reaction; on the other hand, the nanoflower and porous structure are conducive to increasing the active sites, and the mesoporous structure is conducive to the transfer of electrons, so that the material exhibits excellent catalytic performance. The catalyst is mainly used in the discharge chemical reaction of zinc-air batteries. Catalyze the oxygen reduction reaction of the oxygen electrode of the zinc-air battery during the discharge of the battery.

[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Therefore, based on the innovative concept of the present invention,

[0073] Changes and modifications to the embodiments described herein, or equivalent structural or equivalent process transformations made using the contents of the specification and drawings of the present invention, directly or indirectly applying the above technical solutions to other related technical fields, are all included in the protection scope of the patent of this invention.

Claims

1. A nitrogen-doped porous carbon nanoflower catalyst for zinc-air batteries, characterized in that: The catalyst uses green and environmentally friendly amino acids as raw materials, and constructs a special structural morphology by coupling with L-DOPA, which has the function of oxidative self-polymerization. Specifically, amino acid zinc obtained by chelating amino acid with zinc chloride in water bath forms a sheet structure through dehydration condensation of condensing agent, and the added levodopa is also connected with amino acid zinc chelate through condensing agent, and the oxidative self-polymerization function of levodopa is used to assemble the sheet into nanoflower structure, and finally the zinc atoms in the precursor are volatilized at high temperature to obtain nitrogen-doped porous carbon nanoflower catalyst material NCNF-m; The amino acids are glutamic acid and lysine; The amino acid zinc is zinc glutamate and zinc lysine; The molar ratio of the amino acid to zinc chloride is 5:3; The molar ratio of zinc lysine, zinc glutamate and levodopa is 1:1:0.5 to 1:1:

2.

2. A method for preparing nitrogen-doped porous carbon nanoflower catalyst for zinc-air battery, characterized in that: The following steps are involved: Step 1: weigh a certain amount of glutamic acid and dissolve it in deionized water, and add a certain amount of zinc chloride. After dissolution, adjust the pH of the solution and perform chelation in a water bath to form zinc glutamate; Step 2: weigh a certain amount of lysine and dissolve it in deionized water, and add a certain amount of zinc chloride. After dissolution, adjust the pH of the solution and perform chelation in a water bath to form zinc lysine; Step 3: Quantitatively weigh the zinc glutamate and zinc lysine obtained in step 1 and step 2, and add a certain amount of levodopa to dissolve them in an acidic aqueous solution, then add the condensation agent EDC HCl, react for a certain period of time to dehydrate and condense the three, and add DIEA to adjust the pH of the solution to 7, so that it precipitates to form a NCNF-m precursor; The molar ratio of zinc lysine, zinc glutamate and levodopa is 1:1:0.5 to 1:1:2; Step 4: The NCNF-m precursor obtained in step 3 is subjected to high-temperature segmented calcination in a nitrogen atmosphere. First, the material is carbonized by low-temperature calcination to maintain a stable structural morphology. Then, the zinc in the material is vaporized under high-temperature calcination to form a porous carbon material. Finally, the final product NCNF-m is obtained after cooling.

3. The method for preparing a nitrogen-doped porous carbon nanoflower catalyst for zinc-air battery according to claim 2, characterized in that: In the step 1 and the step 2, the molar ratio of glutamic acid and lysine to zinc chloride is 5:

3.

4. The method for preparing a nitrogen-doped porous carbon nanoflower catalyst for zinc-air battery according to claim 2, characterized in that: In the step 1, in the preparation conditions of zinc glutamate, hydrochloric acid and ammonia water are used to make the solution pH=6.5, and the water bath condition is to react at 90° C. for 30 minutes.

5. The method for preparing a nitrogen-doped porous carbon nanoflower catalyst for zinc-air battery according to claim 2, characterized in that: In the step 2, in the preparation conditions of zinc lysine, hydrochloric acid and ammonia water are used to make the solution pH=8, and the water bath condition is to react at 60° C. for 2 hours.

6. The method for preparing a nitrogen-doped porous carbon nanoflower catalyst for zinc-air battery according to claim 2, characterized in that: In the step 3, the acidic condition is pH=4.5-5, and the condensation agent is EDC HCl.

7. The method for preparing a nitrogen-doped porous carbon nanoflower catalyst for zinc-air battery according to claim 2, characterized in that: In the step 3, the reaction time after adding EDC HCl is 2 hours.

8. The method for preparing a nitrogen-doped porous carbon nanoflower catalyst for zinc-air battery according to claim 2, characterized in that: The order of high temperature staged calcination in step 3 is to first heat to 350°C, keep warm for 2 hours, then continue to heat to 1050°C, keep warm for 2 hours, and the heating rate is 2-5°C min -1 .

Citation Information

Patent Citations

  • N-doped microporous carbon sphere ORR catalytic material and preparation method and application thereof

    CN110038612A

  • Preparation method and application of oxygen electrode catalyst Co9S8-porous carbon composite material

    CN111729676A